Perbedaan Lama Waktu Kembali Hamil pada KB Suntik 1 Bulan dengan KB Suntik 3 Bulan di Wilayah Kerja Puskesmas Daya Murni Kabupaten Tulang Bawang Barat Lampung - Ari Julisa Harni; Anita Anita (Jurnal Kesehatan, 2017)
A long time to get pregnant is the lag time of the return of pregnancy after the discontinuation of contraceptive use or after the end of the previous pregnancy. One of the factors that affect the time of return of pregnancy is the use of contraception. According to WHO the time to return pregnant normally is less than 6 months. The purpose of this study was to determine the difference in the duration of re-pregnancy in the mother of 1 month injection acceptor KB with 3 month injection in the work area of Puskesmas Daya Murni Tumijajar District, Regency Year 2017. This type of research is quantitative research. The population in this study were all women hormonal contraceptive mother (1 month injection and 3 month injection) who had been pregnant or have given birth and are currently pregnant with 126 acceptors. The number of samples in this study was 96 respondents. The result of statistic test in obtaining p-value 0.000 which mean at significance value ≤ 0,05 can be concluded there is a difference of mean time duration of pregnancy return between 1 month injection and 3 month injection. Researchers suggest to further researchers to be able to conduct research and studies of other factors that affect the length of time re-pregnant.